Mutualistic relationship between Nitrospira and concomitant heterotrophs. Issue 1 (3rd December 2021) - Murakami, Chiho; Machida, Koshi; Nakao, Yoichi; Kindaichi, Tomonori; Ohashi, Akiyoshi; Aoi, Yoshiteru
Summary: Nitrifying chemoautotrophs support the growth of diverse concomitant heterotrophs in natural or engineered environments by supplying organic compounds. In this study, we aimed to investigate this microbial association, especially (i) to distinguish whether the relationship between nitrifying chemoautotrophs and heterotrophs is commensal or mutualistic, and (ii) to clarify how heterotrophs promote the growth of autotrophic nitrite‐oxidizing bacteria ( Nitrospira ). Pure cultured Nitrospira ( Nitrospira sp. ND1) was employed in this study. Heterotrophs growing with metabolic by‐products of Nitrospira as a sole carbon source were isolated from several environmental samples and used to test the growth‐promoting activity of Nitrospira . Furthermore, liquid chromatography–mass spectrometry analysis was conducted to evaluate how heterotrophs consumed chemical compounds produced by Nitrospira and newly produced during co‐cultivation. Notably, Nitrospira growth was stimulated by co‐cultivation with some heterotrophs and the addition of spent media of some strains, suggesting that not only heterotrophs but also Nitrospira received benefits from their mutual co‐existence. Furthermore, the data suggested that some of the growth‐promoting heterotrophs provided as‐yet‐unidentified growth‐promoting factors to Nitrospira . Overall, Nitrospira and heterotrophs thus appear to exhibit a mutualistic relationship. Such mutualistic relationships between autotrophs and heterotrophs would contribute to the stability and diversity of microbial ecosystems.